2019
DOI: 10.1186/s12890-019-0955-y
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of brain structural alteration in COPD with different levels of pulmonary function impairment and its association with cognitive deficits

Abstract: BackgroundTo explore patterns of brain structural alteration in chronic obstructive pulmonary disease (COPD) patients with different levels of lung function impairment and the associations of those patterns with cognitive functional deficits using voxel-based morphometry (VBM) and tract-based spatial statistics (TBSS) analyses based on high-resolution structural MRI and diffusion tensor imaging (DTI).MethodsA total of 115 right-handed participants (26 severe, 29 moderate, and 29 mild COPD patients and a compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 55 publications
(62 reference statements)
3
41
0
Order By: Relevance
“…In addition, a neuroimaging study showed that corpus callosum integrity is correlated with iSP duration (Fling et al 2013). Therefore, our findings support a functional alteration in the bilateral connectivity in COPD patients and are thus consistent with previous findings of an abnormality in the corpus callosum structure of these patients (Wang et al 2018;Lee et al 2019;Yin et al 2019).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, a neuroimaging study showed that corpus callosum integrity is correlated with iSP duration (Fling et al 2013). Therefore, our findings support a functional alteration in the bilateral connectivity in COPD patients and are thus consistent with previous findings of an abnormality in the corpus callosum structure of these patients (Wang et al 2018;Lee et al 2019;Yin et al 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, chronic obstructive pulmonary disease (COPD) patients display abnormalities in the cerebral structure (Zhang et al 2012;Cullu et al 2013;Zhang et al 2013), including an alteration in corpus callosum structure (Wang et al 2018;Lee et al 2019;Yin et al 2019). This structural alteration of the corpus callosum is known to alter its function (Fling et al 2013;Strauss et al 2019), which might in turn impair bilateral connectivity and subsequently cross-activation when moderate to high muscle force is elicited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 44 Yin et al found that the left-superior frontal gyrus and the right orbital part of the inferior frontal gyrus are strongly associated with pulmonary function (as measured by forced expiratory volume in one second) and cognitive function (as measured by MoCA). 52 Zhang H et al found that the right-inferior triangular frontal gyrus in particular is related to graphic memory. 53 However, the pathological mechanism of GMV atrophy in patients with COPD is very complicated and has not been conclusively demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…9 Although the mechanisms have not been clearly elucidated yet, these may involve chronic hypoxemia, chronic hypercapnia, lung function impairment, systemic inflammation, inactivity, smoking, cerebral atrophy or structural changes and repeated acute exacerbations. [8][9][10] Cognitive dysfunction in COPD is associated with worst outcome such as altered quality of life, 11 higher rate of hospitalization 12 or death, 8,9,12,13 as well as with unsuitable health behavior, such as poor intake of inhaled treatments 14 or difficulties in smoking cessation. 15 However, little is known about its prevalence among those subjects referred for PR 16,17 and how it may affect the benefit or PR.…”
Section: Introductionmentioning
confidence: 99%